Short acting intravenous beta-blocker as a first line of treatment for atrial fibrillation after cardiac surgery: a prospective observational study. (13th June 2022) - Chapalain, X; Oilleau, J F; Henaff, L; Lorillon PharmD, P; Saout, D Le; Kha, P; Pluchon, K; Bezon, E; Huet, O
Abstract: Post-operative atrial fibrillation (POAF) defined as a new-onset of atrial fibrillation (AF) following surgery occurs frequently after cardiac surgery. For non-symptomatic patients, rate control strategy seems to be as effective as rhythm control one in surgical patients. Landiolol is a new highly cardio-selective beta-blocker agent with interesting pharmacological properties that may have some interest in this clinical situation. This is a prospective, monocentric, observational study. All consecutive adult patients (age >18 years old) admitted in the intensive care unit following cardiac surgery with a diagnosed episode of AF were eligible. Success of landiolol administration was defined by a definitive rate control from the beginning of infusion to the 72th h. We also evaluated rhythm control following landiolol infusion. Safety analysis was focused on haemodynamic, renal and respiratory side effects. From 1 January 2020 to 30 June 2021, we included 54 consecutive patients. A sustainable rate control was obtained for 49 patients (90.7%). Median time until a sustainable rate control was 4 h (1, 22). Median infusion rate of landiolol needed for a sustainable rate control was 10 µg/kg/min (6, 19). Following landiolol infusion, median time until pharmacological cardioversion was 24 h. During landiolol infusion, maintenance of mean arterial pressure target requires a concomitant very low dose of norepinephrine. We did not find any other side effects. Low dose of landiolol used for POAF treatment was effective and safe for a rapid and sustainable rate and rhythm control after cardiac surgery.